2017
DOI: 10.1016/j.preteyeres.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oxygen: from animals to humans

Abstract: This article discusses retinal oxygenation and retinal metabolism by focusing on measurements made with two of the principal methods used to study O2 in the retina: measurements of PO2 with oxygen-sensitive microelectrodes in vivo in animals with a retinal circulation similar to that of humans, and oximetry, which can be used non-invasively in both animals and humans to measure O2 concentration in retinal vessels. Microelectrodes uniquely have high spatial resolution, allowing the mapping of PO2 in detail, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
165
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(166 citation statements)
references
References 319 publications
(494 reference statements)
1
165
0
Order By: Relevance
“…The choroidal circulation is thought to provide relatively constant flow, 3336 whereas the retinal circulation varies in response to changes in partial pressure of oxygen (pO 2 ). 37 In recent animal hypoxia experiments by Yi et al, retinal blood flow increased so much that total oxygen extraction actually increased.…”
Section: Discussionmentioning
confidence: 99%
“…The choroidal circulation is thought to provide relatively constant flow, 3336 whereas the retinal circulation varies in response to changes in partial pressure of oxygen (pO 2 ). 37 In recent animal hypoxia experiments by Yi et al, retinal blood flow increased so much that total oxygen extraction actually increased.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen partial pressure varies significantly across neuronal layers. 1,23 The distance between capillaries and the consumption of oxygen determines the relative oxygen content in the immediate environment of each capillary, which may be conceptualized as a cylinder around capillaries (Krogh's cylinder 24 ) although this concept suggests a normoxic/anoxic frontier instead of a continuum. Nevertheless, within a specific layer (i.e., within a given neuronal population) it can be assumed that the distribution of microvessels is paralleled by the local oxygen content and, hence, that the intercapillary distance is a function of the size of Krogh's cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…This rather long pathway may participate in the high coefficient of extraction of oxygen in retinal vessels. 1 The neural consequences of local hypoxia in the retina may be deduced from the Krogh's cylinders concept; that is, the more distant a neuron is from its source of oxygen, the more likely it is to be affected by decreased plasma oxygen saturation. Hence, in case of decreased blood flow without obstruction, hypoxia (and, hence, ischemia) will affect mostly the outer plexiform and inner nuclear layers around collecting venules (i.e., the area most distant from arterioles).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Previous studies suggested that retinal metabolic abnormalities play an important role in the development of DR 2, 4,5 and that rMRO 2 is a potential biomarker for early diagnosis of DR before irreversible damage occurs. [6][7][8] In order to calculate rMRO 2 , we need to measure oxygen saturation (sO 2 ) and the flow rate in major retinal blood vessels, both of which can be effectively quantified simultaneously by visible-light optical coherence tomography (vis-OCT).…”
Section: Introductionmentioning
confidence: 99%